The Effect of Using Number Piggy Bank Media on the Symbolic Thinking Ability of 5-6 Years Old Children - Khoirunnisa, Khiyar; Nurhayati, Eti; Jazariyah, Jazariyah (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The ability to think symbolically is one of the essential aspects of cognitive development to be achieved by early childhood. However, reality shows that some children's ability to think symbolically still needs to be achieved optimally. For this reason, a learning media that functions as an educational game tool is used, namely a number piggy bank. For this reason, this study aims to determine the role of using number piggy banks in learning in early childhood classes in the age range of 5-6 years. Furthermore, it is to determine the effect of using the media on developing their symbolic thinking skills. The type of research used in this study is mixed-method. The data analysis technique used was descriptive and statistical analysis using the chi-squared method (?²). The data collection techniques were observation, tests, interviews, and documentation. The results showed that the number piggy bank was declared to affect symbolic thinking skills in children aged 5-6 at a kindergarten in Kuningan Regency, West Java, Indonesia. It is based on observations of teacher and student activities, which show 82.3% after using the number piggy bank media and 78.6% in the results of symbolic thinking abilities in children aged 5-6 years obtaining BSH qualifications (developing as expected). As well as the results of validity tests and statistical calculations, the use of number piggy banks affects the ability to think symbolically in children aged 5-6 years obtained Z-count (44.15) > Z-table (1.879). Abstrak Kemampuan berpikir simbolik merupakan salah satu aspek perkembangan kognitif yang penting untuk dicapai oleh anak usia dini. Namun realita menunjukkan bahwa kemampuan berpikir simbolik pada beberapa anak masih belum tercapai secara optimal. Untuk itu digunakanlah sebuah media pembelajaran yang sekaligus berfungsi sebagai alat permainan edukatif, yaitu celengan angka. Untuk itu, penelitian ini bertujuan untuk mengetahui peran penggunaan media celengan angka dalam pembelajaran di kelas anak-anak usia dini dalam rentang usia 5-6 tahun. Selanjutnya ialah untuk mengetahui pengaruh penggunaan media tersebut terhadap perkembangan kemampuan berpikir simbolik mereka. Jenis penelitian yang digunakan dalam penelitian ini adalah mixed-method. Teknik analisis data yang digunakan ialah analisis deskriptif dan analisis statistik berupa metode chi-kuadrat (?²). Teknik pengumpulan data yaitu observasi, tes, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa media celengan angka dinyatakan berpengaruh terhadap kemampuan berpikir simbolik pada anak usia 5-6 tahun di TK Negeri Lestari Kecamatan Cibingbin Kabupaten Kuningan. Hal tersebut berdasarkan observasi terhadap aktivitas guru dan siswa yang menunjukkan persentase sebesar 82,3% setelah penggunaan media celengan angka dan 78,6% dihasil kemampuan berpikir simbolik pada anak usia 5-6 tahun memperoleh kualifikasi BSH (bekembang sesuai harapan). Serta hasil uji validitas dan perhitungan secara statistik penggunaan media celengan angka berpengaruh terhadap kemampuan berpikir simbolik pada anak usia 5-6 tahun diperoleh Z-hitung (44,15) > Z-tabel (1,879).